2013
DOI: 10.1620/tjem.231.111
|View full text |Cite
|
Sign up to set email alerts
|

A Greater Reduction of Anterior Cruciate Ligament Elasticity in Women Compared to Men as a Result of Delayed Onset Muscle Soreness

Abstract: Women have a higher risk for anterior cruciate ligament (ACL) injuries compared to men. ACL elasticity and muscle flexibility are major risk factors for knee injuries. The presence of estrogen receptors in connective tissue allows estrogen to change the mechanical properties of muscles and ligaments. Delayed onset muscle soreness (DOMS) happened when begin unaccustomed levels of exercise. Thus, the purpose of this study was to examine ACL elasticity after exercise meant to produce DOMS. As a measure of DOMS, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…An obvious sex-related difference was observed in the role of estrogen in regulating muscle mass and ligament laxity (Lee et al 2013b), and, specifically, its relation to ligament laxity has been investigated (Hansen et al 2009a;Lee et al 2013a). Human connective tissue, such as muscle and ligament, consists of collagen fibers closely packed together.…”
Section: Introductionmentioning
confidence: 99%
“…An obvious sex-related difference was observed in the role of estrogen in regulating muscle mass and ligament laxity (Lee et al 2013b), and, specifically, its relation to ligament laxity has been investigated (Hansen et al 2009a;Lee et al 2013a). Human connective tissue, such as muscle and ligament, consists of collagen fibers closely packed together.…”
Section: Introductionmentioning
confidence: 99%
“…Valuable information with respect to methods to minimise DOMS was provided by the study results of Lee et al [23]. In this study, the rate of the reduction of symptoms related to delayed muscle soreness among women and men was compared, while referring to the risk of ACL damage.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, the authors suggested that women are more vulnerable to damage in the anterior cruciate ligament, and they also return to full fitness after exercise more slowly when compared with men. Therefore, among women, the recovery time after strenuous exercise is lengthened [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some interest in methods of aiding post-exercise biological renovation and reduction of delayed onset muscle soreness can be noticed in the available literature, especially in the area of sports-medicine (Best et al 2008;Lee et al 2013;Bae et al 2014). Kawczyński et al (2013), studying football competitors before the game and after it, showed the differentiation of DOMS symptoms of dominating and non-dominating lower limb muscles.…”
Section: Discussionmentioning
confidence: 99%